Equivalent circuit of a reconfigurable triple‐slot reflectarray cell. Issue 10 (1st July 2016) - Nadaud, Kevin; Gillard, Raphaël; Fourn, Erwan; Gundel, Hartmut W.
Abstract : This study presents an equivalent model for a multiple‐resonance reflectarray cell. It allows predicting the different phase‐states of the cell from only a very few full‐wave simulations. Demonstrations are first given for a passive cell where different geometrical parameters are varied. Then, the approach is generalised to a reconfigurable cell. Finally, a canonical reflectarray with a steered beam has been synthesised in order to illustrate the capabilities of the proposed equivalent circuit.